„TERRORISM”, „TERRORISMS” AND THE PHENOMENON OF TERRORISM’S TENACITY - Прошин, Д.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article is devoted to the phenomenon of terrorism’s tenacity. Notwithstanding its almost complete inability to bring a decisive victory, terrorism remains a substantial factor of the political struggle. It is suggested that the roots of this tenacity are in diversity of forms of terrorist violence, genetically and strategically not related one to another; in terrorism’s comparative efficiency in achieving certain tactical goals; in the presence of narrow group interests that perpetuate terrorist activity, notwithstanding its poor general efficiency.